Generalized dynamic model and control of ambiguous mono axial vehicle robot. (8th September 2016) - Duchon, Frantisek; Rodina, Jozef; Hubinsky, Peter; Rau, David; Kostros, Juraj
This article deals with the novel concept of ambiguous mono axial vehicle robot. Such robot is a combination of Segway and dicycle, which utilizes the advantages of each chassis. The advantage of dicycle is lower energy consumption during the movement and the higher safety of carried payload. The movable platform inside the ambiguous mono axial vehicle allows using the various sensors or devices. This will change the ambiguous mono axial vehicle to the Segway type robot. Both these modes are necessary to control in the stable mode to ensure the safety of the ambiguous mono axial vehicle's movement. The main contents of the article contain description of generalized dynamic model of ambiguous mono axial vehicle and related control of ambiguous mono axial vehicle. The proposal is unique in that the same controller is used for both modes. Several simulations verify proposed control schemes and identified parameters. Moreover, the dicycle type of platform has never been used in robotics and that is another novelty.